AI Writing Tools on the Content and Organization of Students’ Writing: EFL Students’ Perspective - Mursidha, Nur Aini; Fatoni, Mohammad; Putri, Nanin Verina Widya; Tauchid, Ahmad (Universitas Nusantara PGRI Kediri, 2025)
Writing English is a problem for final semester EFL students to complete their thesis. So AI technology becomes a tool that can improve their writing. Researchers conducted this research on three students of English language education at Nahdlatul Ulama Sunan Giri University to find out what AI tools most often use and their perspectives about AI in the content and organization of writing. This research used a qualitative approach through semi-structured interviews. Researchers collected data for this research by conducting pre-observations regarding EFL students who got high writing scores in the previous semester. The first result of this research is the AI tool they used most often was Grammarly, followed by other AI QuillBot, Perplexity AI, DeepL Translator, and Chat GPT. The second result is the respondents gave the positive perspective: AI tools can support, improve and simplify their writing in preparing their theses, and the negative perspective: AI tools must use stable internet data access, usage restrictions and even some AI tools are only intended for premium users. This research can help teachers in the teaching process and development in writing with the help of AI tools. Recommendation for further researchers are to develop this research by using comparison classes and expanding the scope of research and future researchers can develop it by using more research instruments to further strengthen the results.